IoT-based Intelligent Monitoring & Control System Planning Using Project Management Method and Business Feasibility Analysis - Sonki Prasetya; Muhammad Farid Aditya Rahman; Hasvienda M Ridlwan (MBI, 2024)
Various PLTS systems have been installed in the Energy Laboratory of Politeknik Negeri Jakarta, ranging from on grid, off grid, and SHS systems, and various sources of PLTH, PLN, and Generator Set (Genset.) However, the problem that occurs there is that the hybrid system in the Lab. Solar System PNJ room cannot be monitored easily and controlled automatically. As a result of these problems, monitoring the performance of hybrid systems and learning in the PNJ Solar Systems Lab cannot be done optimally. The power source in the lab can be combined in a Hybrid PLTS system and generator with a switch method using the ATS switch control system and monitoring for student learning. The purpose of this research will be to analyze the economic value and use of ATS switches for various concepts in saving electricity in a certain period of time using project management analysis so that it can see the feasibility of this project to be implemented or not. The method in this study is to calculate the economic feasibility value, then find the value of Internal Rate of Return (IRR), NPV, Payback Period using Microsoft excel software and analyze project risks. The results obtained in this project are the IRR value> Interest rate, namely 6.51%> 5.75%. The NPV value obtained is Rp. Rp.572,252 with a payback period in year 12. From the results obtained, this project is declared feasible to continue.